2007
DOI: 10.1007/s11255-006-9025-5
|View full text |Cite
|
Sign up to set email alerts
|

Management of atherosclerotic renovascular disease: the effect of renal artery stenting on renal function and blood pressure

Abstract: In the last few years, renal artery stenting has gradually evolved into one of the most important therapeutic modalities in the management of atherosclerotic renovascular disease. Stenting is nowadays preferred by a steadily increasing number of physicians, not only because of its significant contribution to blood pressure control, but also because of its documented ability to maintain, and even improve, renal function. At the same time, procedure-related morbidity and mortality rates are extremely low, while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Correction of stenosis, with subsequent improvement in renal hemodynamic and hormonal alterations, can potentially lead to a substantial decrease in proteinuria [7].…”
mentioning
confidence: 99%
“…Correction of stenosis, with subsequent improvement in renal hemodynamic and hormonal alterations, can potentially lead to a substantial decrease in proteinuria [7].…”
mentioning
confidence: 99%
“…In several case series, patients whose renal function had been declining before intervention had impressive rates of better renal function afterward [42][43][44] . Muray et al [45] found in a prospective cohort study that a rise in serum creatinine before intervention seems to predict an improvement in renal function after revascularization.…”
Section: Are There Patients Who May Benefit From Endovascular Intervementioning
confidence: 99%